PARTISIPASI MASYARAKAT DALAM MUSRENBANG UNTUK MEWUJUDKAN GOOD GOVERNANCE DI KECAMATAN CIMALAKA KABUPATEN SUMEDANG - Ismaya, Rissa (JRPA - Journal of Regional Public Administration, 2025)
This study aims to analyze community participation in the Development Planning Deliberation (MUSRENBANG) to Realize Good Governance in Cimalaka District, Sumedang Regency. The method used is qualitative. The focus of the study covers four dimensions of community participation according to Cohen and Uphoff's theory, namely participation in decision making, implementation, utilization, and evaluation, as well as inhibiting factors and efforts to increase community participation based on the theory of Nento and Nolfi. The results of the study indicate that community participation in Musrenbang is still not optimal, marked by low levels of attendance, lack of understanding of the Musrenbang process, and negative perceptions of the effectiveness of the activity. Efforts made to increase community participation include increasing socialization, and strengthening community motivation. The conclusion of this study confirms that community participation in Musrenbang requires strengthening in the aspects of public education, transparency of the process, and active involvement in development planning. Recommendations are submitted so that the implementation of Musrenbang can be more inclusive, participatory, and accountable in order to encourage the realization of good governance at the local level.